Personal Hygine Bagi Pedagang Jajanan - Insan, Ranggi Rahimul; Yulastri, Asmar (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2020)
This study aims to find out how the application of personal hygiene for street food traders in Padang Primary Schools can be seen from cleanliness; head, hair, face, nose, ears, mouth, teeth, hands, fingers, skin, and work clothes. This research was conducted in October 2019 at State Elementary School the in Padang. The type of research in this paper is a review using descriptive methods. This research was conducted by distributing questioner. The results of this study indicate that (1) Snack traders in State Elementary School 22 still do not pay attention to the cleanliness of the head and hair. (2) Face and nose hygiene of hawker merchants at 22 Andalas Padang Elementary School, Padang City is still not hygienic (3) Ear cleaning of street hawker vendors at 22 Andalas City Padang, still dirty (4) Oral and dental hygiene of hawker traders in Public Elementary Schools the 22 City of Padang is still dirty (5) Hand and Finger Cleanliness of snacks traders in State Elementary Schools the 22 City of Padang is still dirty (6) Skin hygiene of street vendors in State Elementary Schools the 22 City of Padang is still dirty (7) Cleanliness of work clothes of traders snacks in State Elementary School 22 Andalas Padang City is still lacking.